The impact of community engaged healthcare education on undergraduate students’ empathy and their views towards social accountability; a mixed methods systematic review - Anastasios Plessas; Martha Paisi; Nilufar Ahmed; Zoe Brookes; Lorna Burns; Robert Witton (BMC Medical Education)
Abstract Background Many non-communicable diseases are rooted in social factors that determine health outcomes. Complex topics such as the social determinants of health are difficult to teach through traditional didactic methods. Since the introduction of the social accountability of medical schools’ framework in 1995 by the World Health Organisation, healthcare education institutions are encouraged to shift their traditional education models towards a socially accountable approach. Community engagement can facilitate a deeper understanding of health inequity, barriers to health care, and the social determinants of health whilst enabling institutions to meet their obligation to the communities they serve. This systematic review aimed to answer the following question: ‘‘What is the impact of community engaged healthcare education on undergraduate healthcare students' empathy and their views towards social accountability?’’. Methods This is a mixed-methods systematic review. The protocol was registered with PROSPERO (CRD42022306181). The following databases were searched: Scopus, MEDLINE, Embase, CINAHL, ERIC, BEI for primary research studies published from 1995 to September 2024. Grey literature was also searched via EThOS and Google. Studies recruiting undergraduate students of regulated healthcare professions in countries of very high development were included. A convergent integrated approach to synthesis was followed. Results Out of the 19,590 papers yielded from the literature search, 76 met the inclusion criteria and were included in the review. The following subthemes were generated under three overarching themes: Social accountability (advocacy for action; giving back to the community; bigger picture—identifying social determinants of health and barriers to healthcare; barriers to social accountability), Empathy (humanise community members—everybody has a story; overcome bias and challenge attitudes, assumptions and stereotypes; cultural competence and sensitivity; empathetic communication and interpersonal skills; feeling sympathy and sadness), and Shaping the future workforce (future professional demeanour; professional interests; interprofessional education and collaboration). Conclusions Community engaged education can help students better understand community needs, social determinants of health, improve empathy and cultural sensitivity, and build advocacy for social justice and change.